Digital innovation, human capital allocation, and labour share: Empirical evidence from listed companies in China - Hongcheng Ling; Xuebin Ding; Changqi Tao (Journal of Innovation & Knowledge (JIK), 2025)
Digital technology is increasingly blurring the lines between humans and machines, significantly influencing the distribution of income among workers. The question of how businesses can capitalise on the benefits of digital advancement by optimising internal human capital allocation during the digital innovation process has become a critical concern. This study utilises the Sentence-BERT(SBERT) model to identify digital innovation and examines its effects on the labour share within firms, alongside the underlying mechanisms from the viewpoint of human capital allocation. The research findings are as follows: First, digital innovation has a positive and significant impact on the labour share, a conclusion that remains robust after conducting various sensitivity tests and addressing endogeneity issues. Second, the mechanism analysis reveals that changes in human capital allocation serve as a crucial mediating factor between digital innovation and labour share. Further exploration indicates that skills training, as an element of human capital allocation, demonstrates varying levels of influence across various company sizes and industry characteristics. Third, the positive impact of digital innovation on labour share is more pronounced in regions with supportive business environments, high-tech sectors and firms with superior corporate governance. Lastly, for ordinary employees, digital innovation enhances their labour share. Conversely, for management, while digital innovation reduces their labour share, it increases their equity incentive, suggesting that digital innovation aids in bridging the digital divide within firms and fosters a more equitable distribution of benefits. This study not only enriches the theoretical understanding of the effects of digital innovation on labour income but also encourages the practical application of digital innovation in reducing the wealth gap and achieving shared prosperity.
Keywords: J21; O15; O33; 650; Digital innovation; Human capital allocation; Labour Share; Digital divide